OIL FLAX GROWING FEATURES IN WESTERN POLISSYA CONDITIONS - Онюх, Ю. М. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The cultivation of flaxseed oil on the territory of Western Polissya has a number of features related to the height of the stem and unstable weather conditions. The purpose of the research was to determine the patterns of weather conditions influence on the duration of oil flax growing season and adaptation of the technological process of harvesting and processing of the stem portion of the crop, depending on the phase of culture’s ripeness At high temperature parameters with low humidity, harvesting with a grain harvester is possible in the phase of early yellow maturity after the processing of desiccant. At the same time, the term transformation of straw into a treated fibres increases. In growing season with reduced temperature and high humidity harvesting should be carried out by the method of pulling stems with simultaneous cutting of apical part of plants with a combine harvester